Interpretation of Work Meaningfulness as a Trigger for Self-Driven Motivation in KSPPS Employees of KSPPS BMT Mandiri Sejahtera East Java - Syuhada'; Intan Ayu; Andini Ardy Margareta (Journal of Economics and Social Sciences (JESS), 2026)
This study examines how employees of KSPPS BMT Mandiri Sejahtera East Java interpret the meaning of their work and how these interpretations foster self-driven motivation. In Islamic microfinance institutions, work extends beyond economic objectives to encompass social and religious responsibilities, making work meaningfulness an important source of intrinsic motivation. This study employs a qualitative phenomenological approach. Data were collected through in-depth interviews, observation, and documentation involving employees of KSPPS BMT Mandiri Sejahtera East Java and analyzed using the Miles and Huberman interactive model, including data reduction, data display, and conclusion drawing. The findings indicate that employees perceive work as an act of worship, a trust, a form of community service, and a means of empowering the local economy. These interpretations are shaped by the interaction of personal values, organizational culture, leadership, and the social environment. Meaningful work encourages self-driven motivation, reflected in employees' initiative, responsibility, commitment, perseverance, and enthusiasm without relying primarily on external rewards. The study concludes that work meaningfulness is a key psychological foundation for developing sustainable intrinsic motivation in Islamic microfinance institutions. These findings contribute to the literature on meaningful work and provide practical insights for strengthening human resource management through the integration of organizational and Islamic values.